Phanerozoic mafic magmatism in the southern Siberia craton: geodynamic implications - Gladkochub, D.; Donskaya, T.; Ivanov, A.; Ernst, R.; Mazukabzov, A.; Pisarevsky, Sergei; Ukhova, N. (ELSEVIER SCIENCE BV, 2010)
The Phanerozoic history of mafic magmatism in the southern Siberian craton included three major events. The earliest event (∼500 Ma) recorded in dolerite dikes occurred during accretion and collision at the early stage of the Central Asian orogen. Injection of mafic melts into the upper crust was possible in zones of diffuse extension within the southern Siberian craton which acted as an indenter. The Late Paleozoic event (∼275 Ma) produced dikes that intruded in a setting of subduction-related extension at the back of the active continental margin of Siberia during closure of the Mongolia–Okhotsk ocean, as well as slightly older volcanics (290 Ma) in the Transbaikalian segment of the Central Asian orogen. Early Mesozoic magmatism in the southern Siberian craton resulted in numerous 240–250 Ma mafic intrusions in the Angara–Taseeva basin. The intrusions (Siberian traps) appeared as the subducting slab of the Mongolia–Okhotsk ocean interacted with a lower mantle plume. The post-Late Paleozoic ages of flood basalts (290–275 Ma) correspond to progressive northwestward (in present coordinates) motion of the slab beneath the southern craton margin which likely ceased after the slab had reached the zone of the Siberian superplume. Since its consolidation after the Early Mesozoic activity, the crust in the area has no longer experienced extension favorable for intrusion of basaltic magma.